The social production of knowledge on contemporary migratory processes - Betrisey Nadali, Débora (2005)
Nowadays, the constant and permanent geographic mobility and the settling of poor migrants gives rise to production processes of other stigmatized people who are available for the work of the imagination or of manipulation. The objective of this paper is to analyze the role that certain specialists in social sciences have had and the use of their output and knowledge, in the frame of a social demand of representations and visions of the migratory phenomenon of the borders, generated in Argentina during the nineties.